Childhood Adversity and Co-Dependency Roles in a Case of a Midwife with Pethidine use Disorder Attending Mulago National Referral Hospital, Kampala, Uganda - Odokonyero, Raymond; Aujo, Tabitha; Agaba, Denis; Abbo, Catherine (Cogent Public Health, 2022)
Pethidine is a short and fast-acting synthetic opioid that has a high potential for abuse and addiction compared to other opioids. It is popularly used in the management of pain such as pancreatitis, and cholecystitis peri- and post-operations. Among patients, addiction to pethidine is usually induced unintentionally by a health worker in the course of treating the patient’s pain. Addiction to pethidine is a common but silent problem for healthcare workers such as doctors, nurses, and midwives, and it is often underreported. Childhood adversity and co-dependency roles by family members have been linked to the development and maintenance of addiction to psychoactive substances including pethidine. This case study on a midwife with pethidine addiction in Uganda is a call to draw attention to childhood adversity and co-dependency roles in pethidine addiction.
Keywords: Pethidine; Midwife; Childhood adversity; Co-dependency